Embedding employABILITY thinking across higher education : final report. - Bennett, Dawn (Australia. Dept of Education, Skills and Employment, 2020)
University educated workers are critical to Australia’s economic health, international standing and social wellbeing, but if graduates are to meet their full potential they need to have developed, as students, the ability to find, create and sustain meaningful work across the career lifespan and in multiple contexts. This is employability in the higher education context. The fellowship reported here sought to enable the sector to undertake this development. EmployABILITY thinking is a strength-based, metacognitive approach to employability development which is delivered within the existing curriculum without additional time, expertise or resources. The approach prompts students to understand why they think the way they think; how to critique and learn the unfamiliar; and how their values, beliefs and assumptions can inform and be informed by their learning, lives and careers. As suggested by its use of capitals, rather than focus on learners’ potential to be employed and directed by others, the approach focusses on learners’ ABILITY to create and sustain meaningful work. This ability is as relevant to workers in traditional, full-time employment with a single employer as it is to workers who combine multiple roles to create portfolios of work. Higher education employability frameworks, policies and initiatives have little impact unless they connect with students, yet most employability development activities are co-curricular and attract the students who need them least. Initiatives within the curriculum tend to be program-wide streams or distinct modules that are separated from the discipline studies in which students want to engage. Only when employability development and career guidance are aligned with disciplinary knowledge, skills and practices will it become core business. [Executive summary, ed]